Add-on-Statin Extended Release Nicotinic Acid/Laropiprant but Not the Switch to High-Dose Rosuvastatin Lowers Blood Pressure: An Open-Label Randomized Study. (15th May 2011) - Kei, Anastazia; Elisaf, Moses; Moutzouri, Elisavet; Tsiara, Stavroula; Liberopoulos, Evangelos
Abstract : Introduction . Nicotinic acid (NA) and statins have been associated with reductions in blood pressure (BP). Patients and Methods . We recruited 68 normotensive and hypertensive dyslipidemic patients who were treated with a conventional statin dose and had not achieved lipid targets. Patients were randomized to switch to high-dose rosuvastatin (40 mg/day) or to add-on current statin treatment with extended release (ER) NA/laropiprant (1000/20 mg/day for the first 4 weeks followed by 2000/40 mg/day for the next 8 weeks) for 3 months. Results . Switching to rosuvastatin 40 mg/day was not associated with significant BP alterations. In contrast, the addition of ER-NA/laropiprant to current statin treatment resulted in a 7% reduction of systolic BP (from134 ± 12 to125 ± 10 mmHg, P < .001 versus baseline andP = .01 versus rosuvastatin group) and a 5% reduction of diastolic BP (from81 ± 9 to77 ± 6 mmHg, P = .009 versus baseline andP = .01 versus rosuvastatin group). These reductions were significant only in the subgroup of hypertensives and were independent of the hypolipidemic effects of ER-NA/laropiprant. Conclusions . Contrary to the switch to high-dose rosuvastatin, the addition of ER-NA/laropiprant to statin treatment was associated with significant reductions in both systolic and diastolic BP.